The Moderating Role of Family Harmony in the Relationship Between Resilience and Suicidal Ideation Among University Students - Syola, Devi Uli Grace; Soetikno, Naomi; Satiadarma, Monty P. (International Journal of Science and Society, 2025)
Suicidal ideation among college students is a significant mental health issue that requires serious attention. This study aims to examine the role of family harmony as a moderator in the relationship between resilience and suicidal ideation in college students. The study used a quantitative approach with a non-experimental design and convenience sampling method. A total of 388 college students aged 18-25 years old who live with or regularly interact with their families participated in an online survey using the Beck Scale for Suicide Ideation (BSSI), Connor-Davidson Resilience Scale (CD-RISC), and Family Harmony Scale (FHS-24). The results of the moderation regression analysis showed that resilience has a significant negative relationship with suicidal ideation, which means that the higher a person's resilience, the lower the tendency of suicidal ideation. In addition, family harmony acted as a moderator in this relationship; students with high resilience from harmonious families showed lower levels of suicidal ideation compared to those from less harmonious families. These findings confirm the importance of family support and strengthening resilience as protective strategies to prevent suicidal ideation among college students. The implications of this study lead to the development of intervention programs that focus on coping training, psychological counseling, and family education to improve the mental well-being of university students.